PENGARUH PENAMBAHAN CMC TERHADAP KARAKTERISTIK ES KRIM JUS BUAH PEDADA DAN KELAPA MUDA [CMC Addition Effect on Characteristics of Ice Cream Made from Pedada Fruit and Young Coconut Juices] - Jariyah Jariyah; Rudi Nurismanto; Nur Fitri Dian Pratiwi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2019)
Pedada fruit contains 56.74 mg/100 g of vitamin C and 79% of water. One of the uses of this fruit is for a raw material of fruit ice cream. Objectives of this research was to evaluate quality of fruit ice cream made from padada fruit and young coconut juice with addition of Carboxy Methyl Celulose (CMC). Randomized completely design with two factors was implemented in this research. The first factor was proportions of pedada fruit and young coconut juice consisting of three levels, that was i.e., 25%:75%, 50%:50%, and 75%:25%. The second factor was CMC concentrations consisting of three levels, that was i.e., 0.1, 0.2, and 0.3%. The best quality of fruit ice cream was obtained from 25% padada fruit juice and 75% young coconut juice with addition of 0.3% CMC. The physical and chemical characteristics of the ice cream were a melting time of 11.11minute/10g, an overrun of 5.71%, a relative viscosity of 8.15 (Poiseuille x103), a fat content of 0.06%, a protein content of 1.29%, and a vitamin C content of 0.76mg/10g. The sensory characteristics of the ice cream were brownish, rather sour and sweet, and pedada-fruit aroma.